PENGARUH GAYA KEPEMIMPINAN DELEGATIF, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK MANDIRI KCP JAKARTA KOTA - Christina Catur Widayati; Septy W; Thea H. Rahardjo (Fakultas Bisnis UKDW, 2016)
This research aims to know the influence of leadership styles, work motivation and discipline onperformance of employees at Mandiri Bank Branch Jakarta Kota. As for the methods used in thisstudy using the method of quantitative research. And the samples used in this study as many as 40employees. This research uses the sampling method is saturated, whereas the methods of analysisused was multiple linear regression analysis. The results showed that leadership style, workmotivation and discipline significant effect on performance of the employees. the leadership styleeffect positively on performance of the employees. The motivation of working in a positive effect onperformance of the employees. The discipline of working in a positive effect on performance of theemployees.Keywords: Leadership style, work motivation, performance of the employees